A Juridical Analysis of Copyright for Artificial Intelligence-Generated Works in the Education Sector - Denty Maretasari; Santi Widiasari; Ahmad Ma’mun Fikri (PDIH Untag Semarang, 2025)
The rapid development of Artificial Intelligence in the education sector presents new legal challenges, particularly regarding copyright ownership of autonomously produced works. The 2014 Copyright Law does not yet regulate the status of AI as a creator, creating a legal vacuum. This research aims to examine copyright regulations for AI works, the possibility of AI becoming a limited legal subject, and the urgency of updating regulations regarding ownership and attribution of AI-based works in the education sector. This research uses a normative juridical method with a doctrinal approach to analyze the legal certainty and legal implications of AI-based works in the education sector. The research finds that AI-based works lack legal certainty under the Copyright Law, creating a regulatory vacuum and potential disputes. The analysis demonstrates the need to recognize Artificial Intelligence as a limited legal subject to clarify attribution, ownership, and responsibility for the works it produces. The research concludes that the Copyright Law is inadequate to address AI works, and therefore legal reform is necessary for the sake of certainty and protection of rights. New, adaptive and collaborative arrangements are needed to enable Indonesia’s legal system to accommodate AI developments and support a technology-based education ecosystem.